GEOMETRIC PUZZLE DAN ART THERAPY (PLATE ART COLLAGE) UNTUK MENINGKATKAN KONSENTRASI DAN INTERAKSI SOSIAL ANAK RETARDASI MENTAL DI SLB BC YATIRA - Megasari, Mona; Riyanto, Agus (JURNAL KESEHATAN KARTIKA, 2023)
Background: Inadequate food availability both in terms of quantity, nutritional value, and lack of variety of food types, as well as poor parenting, all have an impact on the problem of stunting. To change behavior that can lead to improved nutritional health of mothers and children, education is needed. This is because the poor nutritional status of pregnant women greatly affects the nutritional status of pregnant women. Objective : The study was conducted to determine the differences in the level of knowledge and attitudes before and after health education regarding the incidence of stunting. Method;This research is a pre-experimental research with one group pretest-posttest design. Researchers conducted research on the effect of health education with E-Module media on knowledge and attitudes of pregnant women about stunting. Data were collected by giving questionnaires to 16 respondents of pregnant women before and after being given health education. From the two variables that have been calculated by a computerized system with the results of the analysis of the dependen t test, the knowledge value (p= 0.0001) and attitude (p= 0.003) 0.05. Results: Concluded that there is an effect of health education with E-Module media on increasing knowledge and attitudes of pregnant women about the incidence of stunting in the working area of ​​Batujajar Health Center. Conclusion; It is hoped that the results of this study can be used as input to improve the quality of services, especially health education with E-Module media and increase public knowledge and attitudes about stunting. Research results can be used and beneficial for future researchers as information and reference material for researchers on health education.